The Effect of COVID-19 on Male Sex Hormones: A Meta-Analysis of Prospective Cohort Study - Xiucheng Lan; Diang Chen; Meijing Wang; Xujun Yu; Liang Dong; Junjun Li; Degui Chang; Fang Yang (Springer, 2024)
Abstract Purpose To evaluate the possible effects of novel coronavirus disease 2019 (2019-NCOV) on male sex hormones and reproductive ability, and analyze its incidence and risk factors. Methods We retrieved from PubMed, Embase, The Cochrane Library, Web of Science, Clinical Trails, CNKI, CBM, Wan Fang Database and VIP to collect research on the effects of COVID-19 on the male sex hormone. Our literature search was conducted until April 2022, and two investigators independently screened articles based on inclusion and exclusion criteria. In strict accordance with the inclusion and exclusion criteria, two researchers independently screened the literature and comprehensively analyzed 8 cohort studies on the impact of COVID-19 on male sex hormone. And We used RevMan5.4.1 and Stata15.0 for statistical analysis. Finally, there were eight cohort studies on the effects of COVID-19 on male sex hormones. Results T(RR = − 3.94; 95% CI − 6.22, − 1.66; P = 0.0007), testosterone in the COVID-19 group decreased by 3.94 nmol/L compared with the control group, and the difference was statistically significant. LH (RR = 0.85; 95% CI − 0.26, 1.96; P = 0.13), the LH in COVID-19 group was 0.85 mlU/ml higher than that in control group, but the difference was not statistically significant. FSH (RR = 0.25; 95% CI − 0.72, 1.23; P = 0.61), the FSH of COVID-19 group was 0.25 mlU/ml higher than that of the control group, but the difference was not statistically significant. PRL (RR = 2.42; 95% CI 0.52, 4.31; P = 0.01), the PRL in the COVID-19 group was 2.42 ng/ml higher than that in the control group, and the difference was statistically significant. E2(RR = 11.88; 95% CI 9.90, 13.86; P < 0.00001), The level of E2 in the COVID-19 group was 11.88 pg/ml higher than that in the control group, and the difference was statistically significant. T:LH (RR = − 0.39; 95% CI − 076, − 0.02; P = 0.04), the ratio of T:LH in COVID-19 group was lower than that in control group, and the difference was statistically significant. FSH:LH (RR = − 0.38; 95% CI − 0.86, 0.11; P = 0.13), the ratio of FSH:LH decreased in COVID-19 group compared with control group, but the difference was not statistically significant. Conclusions COVID-19 can affect the level of sex hormones, especially T, which may further affect male fertility. Due to the limitations of this study, this conclusion needs to be further verified by large-sample, high-quality prospective cohort studies on the long-term effects of COVID-19 on male sex hormones and fertility.